Cross-sectional, multicenter study comparing sex differences in patients undergoing endovascular repair of infrarenal abdominal aortic aneurysms. Results from the São Paulo State University Provincial Hospitals Registry (RHEUNI) - Moura, Regina [UNESP]; Joviliano, Edwaldo Edner; Guillaumon, Ana Terezinha; Raymundo, Selma Regina de Oliveira; Hafner, Ludwig; Sobreira, Marcone Lima [UNESP]; Almeida, Marcelo Jose de; Miquelin, Daniel Gustavo; Geiger, Martin; Yoshida, Winston Bonetti [UNESP] (Soc Brasileira Angiologia Cirurgia Vascular-sbacv, 2024)
Background: Abdominal aortic aneurysms (AAA) are 4-6 times more frequent among men than among women, but prognosis tends to be worse in women. Objective: To compare endovascular procedures to repair infrarenal AAA in men and women, using data from a prospective registry. Methods: This registry collected data from five university hospitals in the state of S & atilde;o Paulo (Brazil) from 2012 to 2022. A cross-sectional study was conducted compiling demographic data, anatomic variables (aneurysm diameter, short neck, angulated neck, calcified neck, or thrombosed neck; distal neck < 1.5 cm, and tortuous, abnormal iliac arteries), complications (leaks, conversions, and patency or stenosis of branches) and renal failure and mortality at 30 days. The chi-square test and Student's t test were applied with a 5% significance level. The study was approved by the Ethics Committee (process 4040-2011). Results: A total of 152 (15.9%) of the patients were women and 799 (84.0%) were men (p < 0.05). The majority were white (80.2% of the women and 87.4% of the men). Diabetes and hypertension were significantly more frequent among the women. The most prevalent shape was fusiform, particularly among the women (95.39% vs. 89.86% among men). Mean diameter was smaller among the women (5.96 cm vs. 6.49 cm; p = 0.0056). The iliac arteries were less often involved among the women (89.40% vs. 73.58%; p = 0.00001). Blood loss was greater in the men (321.40 ml vs. 168.84 ml among the women; p < 0.05). Operative mortality was similar in both sexes, but obstructions were more frequent among the women (15.2% vs. 13.51%; p = 0.017296). Conclusions: Aneurysmal diameter was smaller and obstructive complications were more frequent among women.
Keywords: abdominal aortic aneurysm; endovascular procedures; postoperative complications; sex distribution studies; mortality